اللغة والتعليم والتنمية - فلوح, أحمد (جامعة الوادي - University of Eloued, 2020)
اللغة احد اهم المقومات الاساسية لأي مجتمع، نظرا لأهمية الوظائف الاجتماعية التي توفرها لأفراد المجتمع، وأهمها انها وسيلة الاتصال والتواصل بين افراد المجتمع، وأساس التماسك الاجتماعي، وحاملة وناقلة القيم والتراث من جيل الى جيل. والعلاقة بين اللغة والتعليم والتنمية علاقة مترابطة فتاريخ الامم وحاضرها يثبت ان اللغة اساس التعلم والتعليم وأساس التنمية، وان نجاح التنمية من نجاح التعليم، والتعليم أداة نجاحه اللغة. فإذا اردنا تطوير المجتمع وتنمية افراده وتربيتهم وتعليمهم، وتمتين ثقافتهم وترسيخ هويتهم، علينا بالاستفادة من مختلف الوظائف الاجتماعية التي تتيحها اللغة، وان نجعل اللغة اداة فعالة في عملية التربية والتعليم، واداة للتنمية المنشودة Language is one of the most important fundamentals of any society because of the importance of the social functions it provides to the members of the society, the most important being the means of communication among the members of society, the basis of social cohesion, the carrier of values and heritage from generation to generation.The relationship between language, education and development is interrelated. The history of the nations and their present proves that language is the basis of learning, education and the basis of development. The success of development is the success of education. we want to develop society, develop its members, educate them, strengthen their culture and establish their identity, we must take advantage of the various social functions offered by the language, make language an effective tool in the process of education and a tool for development
Langage, éducation and développement
مقال بمجلة السراج في التربية وقضايا المجتمع . مج 04 ع01. أوت 2020 . جامعة الوادي
Keywords: اللغة- خصائص اللغة- وظائف اللغة- اللغة والتعليم- اللغة والتنمية; language - language characteristics - language functions - language and education - language and development